A confused regulation and some suggestions «de iure condendo»: Notes on the can. 1071, §1.4; 1086; 1117 and 1124 - Callejo de Paz, Rufino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The situation of some Catholics who have abandoned their faith or the Church is taken up in the Code of Canon Law with two formulations: notorious abandonment of their faith, canon 1071, §1.4, and withdrawal from the Church by a formal act, canons 1086, 1117 and 1124. At a marriage level the consequences are very different, depending on the various situations. The problems discerned in these cases from the point of view of doctrine and legal pastoral practice are several and different. After stating the main doctrinal positions we suggest in line with an important doctrinal sector some considerations in view of a future remodelling of this matter.
Keywords: Abandonment; withdrawal; notorious; formal; apostasy; schism; exemption; canonical form; mixed marriages and disparity of worship marriages